2016
DOI: 10.1007/s12041-015-0602-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping and QTL analysis of agronomic traits in Indian Mucuna pruriens using an intraspecific F2 population

Abstract: Mucuna pruriens is a well-recognized agricultural and horticultural crop with important medicinal use. However, antinutritional factors in seed and adverse morphological characters have negatively affected its cultivation. To elucidate the genetic control of agronomic traits, an intraspecific genetic linkage map of Indian M. pruriens has been developed based on amplified fragment length polymorphism (AFLP) markers using 200 F₂ progenies derived from a cross between wild and cultivated genotypes. The resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Although we focused on molecular pumpkin breeding from conventional to organic farming in Hawai'i, this strategy can be applied to any crop whose main production occurs in a conventional setting and consumers demand an organically grown alternative. Indeed, we found that new technologies were as successful in this understudied system as in others [29,30]. Furthermore, our genetic and genomic information can be used to improve the genome assembly of pumpkin.…”
Section: Discussionmentioning
confidence: 90%
“…Although we focused on molecular pumpkin breeding from conventional to organic farming in Hawai'i, this strategy can be applied to any crop whose main production occurs in a conventional setting and consumers demand an organically grown alternative. Indeed, we found that new technologies were as successful in this understudied system as in others [29,30]. Furthermore, our genetic and genomic information can be used to improve the genome assembly of pumpkin.…”
Section: Discussionmentioning
confidence: 90%